2012
DOI: 10.4194/1303-2712-v12_2_25
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Long-term study (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) of the Black Sea turbot spawning population in Sevastopol region (Crimean coast, Ukrainian sector of the Black Sea) was carried out on the basis of monitoring of the turbot gill net catches. Despite some signs of recovery of BST local population during 2009-2010, analysis revealed numerous signs of absence of stability in the local turbot population: low sizes of spawners in comparison with other Black Sea areas, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Among S. maeoticus specimens collected and analyzed in 2017, a higher number of bacteria was reported than in the previous year, with the maximum bacterial load in fish from stations 2 (4 × 10 3 CFU/g), 3 (1 × 10 4 CFU/g) and 11 (2 × 10 4 CFU/g), where the depth was between 38 and 61 m, and we add that the specimens analyzed were large, and showed visible signs of illness (Figure 6).…”
Section: Bacterial Diseases and Their Impact On S Maeoticus Populatio...mentioning
confidence: 88%
See 1 more Smart Citation
“…Among S. maeoticus specimens collected and analyzed in 2017, a higher number of bacteria was reported than in the previous year, with the maximum bacterial load in fish from stations 2 (4 × 10 3 CFU/g), 3 (1 × 10 4 CFU/g) and 11 (2 × 10 4 CFU/g), where the depth was between 38 and 61 m, and we add that the specimens analyzed were large, and showed visible signs of illness (Figure 6).…”
Section: Bacterial Diseases and Their Impact On S Maeoticus Populatio...mentioning
confidence: 88%
“…Researchers from the Biological Station of Sevastopol (BBS) conducted a first attempt to assess the health status of the S. maeoticus spawning population from 2007 to 2010. The preliminary health status analysis showed that at least 20% of adult fish showed clear signs of various diseases [3].…”
Section: Discussionmentioning
confidence: 99%
“…As a follow-up, the Scientific, Technical and Economic Committee for Fisheries (STECF) assessed the updated Joint Recommendation presented and noted that improvements to the information provided were needed. The Commission has recognised the existence of scientific studies demonstrating the high survivability of turbot caught by vessels from non-EU countries fishing with gillnets in the Black Sea (Bașaran & Samsun, 2004;Samsun & Kalayci, 2005;Giragosov & Khanaychenko, 2012). Having regard to the fact that the studies cited relate to the same maritime basin, the same species and gears as included in the exemption requested by Romania and Bulgaria, the Commission considered that this Joint Recommendation should be taken into account for the purposes of granting the exemption.…”
Section: Aims and Backgroundmentioning
confidence: 99%
“…Formally, this species is managed as a single stock across the Black Sea (GFCM 2019), although localized subpopulations do exist (Giragosov and Khanaychenko 2012) and there remains the need to account for those units in spatially resolved stock assessment models (M. Cardinale pers. comm.…”
Section: Atlanticmentioning
confidence: 99%